The Strength of an Accounting Firm’s Ethical Environment and the Quality of Auditors’ Judgments - Martinov-Bennie, Nonna (Journal of business ethics, 2009)
This study examines the impact of the strength of an accounting firm’s ethical environment (presence and reinforcement vis-à-vis the presence of a code of conduct) on the quality of auditor judgment, across different levels of audit expertise. Using a 2 × 2 full factorial ‹between subjects’ experimental design, with audit managers and audit seniors, the impact of different levels of strength of the ethical environment on auditor judgments was assessed with a realistic audit scenario, requiring participants to make judgments in respect of an inventory writedown. Based on prior research, and as hypothesized, participants possessing greater auditing experience made higher quality technical judgments. While there were no significant differences between the quality of audit judgments made by participants in the stronger ethical environment, over-all results indicate that managers are more sensitive to differences in the strength of the ethical environment than seniors. This is consistent with the hypothesis, and with prior research which suggests that the impact of the code will only be significant if it has been bilaterally internalized by individuals. This has important implications for accounting firms and regulators, given that the International Standard on Quality Control 1, requires the communication and reinforcement of ethical principles as part of firms' quality control processes. It suggests that firms will need to carefully consider the means by which they communicate and reinforce ethical principles, as it is possible to differentially impact auditors of different rank.